Blockchain technology in supply chain management - automotive industry - Lee, Sherwin Ler Yang (Nanyang Technological University, 2022)
The automotive industry is a particularly promising application case for blockchain technology adoption. It creates opportunities for manufacturers to increase their tracking capabilities to meet the increasing demand for supply chain visibility. This paper examines industry insights through interviews with industry practitioners and managers to explore the existing challenges of adopting blockchain technology in the upstream automotive supply chain. The findings suggest that blockchain is a viable solution for the issues facing the automotive industry, such as product recalls and increased supply chain disruptions. However, the lack of understanding of the technology and difficulty in integrating the technology into current processes may hinder the acceleration of industry-wide applications. The possible solutions for these challenges include increasing awareness and education, to make it less daunting to understand the technology. In addition, companies can form consortiums and strategic alliances to increase collaboration and benefit the industry. Furthermore, industry standards can be established to reduce administrative burden and complexity of cross-system communications.